O design gráfico como linguagem em fluxo: um estudo de caso - Gouvêa, Aurélio Homobono (2018)
This research analyzes and studies graphic design investigative process while rethinking its concept, since, as a practice, its creative potential must be adressed rather than its productive facet. As a consequence we must reflect about its epistemology. Graphic design was constituted under a rhetoric responsible for favoring certain economic interests emphasizing its programmatic face. In this sense, it is necessary to reflect on the normatization of the practice and on the strategies used to subvert it, generating new ways of communicating. Therefore, the research asks the following question: How does the graphic designer creative process acts as a way of producing knowledge? In order to try to answer such questioning, we decided to study Stefan Sagmeister’s creative process both in its analogue and digital phase to verify the strategies he uses to question a certain pattern of graphic design instituted by the industry. The main hypothesis of this research corresponds to the analogy as a guiding strategy of the designer creation procedures that, in turn, leads him to question the methodology to which his practice corresponds. These factors generate a metacontextual leap that forces us to review the conceptual bases of the area. The general objective is to understand, based on his work, how the graphic designer proposes new ways of communicating and knowing the space, thus generating new meanings about the area. The specific objectives are: to analyze the characteristics that constitute the rhetoric of graphic design as a resistance to industrial functionalization, to study how the procedures adopted by the chosen empirical object act as a breakdown of the normalization of a certain type of graphic design, verify the insertion of graphic design investigative and professional practice as a producer of knowledge in the field of communication and analyze how Sagmeister creative process is in line with a change in the concept of design. The research theoretical reference contemplates authors who study the relation between language and politics, such as Maurizio Lazzarato, Roland Barthes, Walter Benjamin and Ernesto Laclau; the disciplinary and control society, Michel Foucault and Gilles Deleuze; theorists oriented to the evolution of the media and the communication as a science like Vilém Flusser, Lucrécia Ferrara, Friedrich A. Kittler and Marshall McLuhan, as well as the considerations of Charles Sanders Peirce, Gregory Bateson and Paul Valéry in order to investigate the evolutionary traits of language